Successful laparoscopic management of combined traumatic diaphragmatic rupture and abdominal wall hernia: a case report - Sze, Li Siow; Chee, Ming Wong; Mark, Hardin; Mushtag, Sohail (BioMed Central, 2016)
Background: Traumatic diaphragmatic rupture and traumatic abdominal wall hernia are two well-described but rare clinical entities associated with blunt thoracoabdominal injuries. To the best of our knowledge, the combination of these two clinical entities as a result of a motor vehicle accident has not been previously reported. Case presentation: A 32-year-old Indian man was brought to our emergency department after being involved in a road traffic accident. He described a temporary loss of consciousness and had multiple tender bruises at his right upper anterior abdominal wall and left lumbar region. An initial examination revealed blood pressure of 99/63 mmHg, heart rate of 107 beats/minute, and oxygen saturation of 93 % on room air. His clinical parameters stabilized after initial resuscitation. A computed tomographic scan revealed a rupture of the left diaphragm as well as extensive disruptions of the left upper anterior abdominal wall. We performed exploratory laparoscopic surgery with the intention of primary repair. The diaphragmatic and abdominal wall defect was primarily closed, followed by reinforcement with PROLENE onlay mesh. The patient’s postoperative recovery was complicated by infected hematomas over both flanks that were managed with ultrasound-guided percutaneous drainage. He was discharged well despite a prolonged hospital stay. Conclusions: We present a complex form of injuries managed successfully via a laparoscopic approach. Meticulous attention to potential complications in both the acute and convalescent phases is important for achieving a successful outcome following surgery.